PENDIDIKAN AGAMA ISLAM DALAM PERSPEKTIF TEKSTUALIS NORMATIF DAN KONTEKSTUALIS HISTORIS - Karimullah, Karimullah (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2017)
This paper seeks to describe the dichotomic-paradoxical perspectives surrounding Islamic religious education. On the one hand, the character of Islamic religious education has a normative textual perspective which has implications for the realization of an autistic Islam that gave birth to radicalism. On the other hand, historical contextual perspectives that emphasize religious dialectics with local cultures with the implications of respecting plurality and are highly anti-relying on authenticity. This paper itself suggests the need for maturity, maturity, attitude of responsibility and awareness in determining the choice of each of the two.